Developing Core Indicators for Evaluating Second Victim Programs: An International Consensus Approach - Sofia Guerra-Paiva; Sofia Guerra-Paiva; Irene Carrillo; José Mira; José Mira; Joana Fernandes; Reinhard Strametz; Eva Gil-Hernández; Paulo Sousa; Paulo Sousa (Frontiers Media S.A., 2024)
ObjectivesTo establish a consensus for evaluating second victims (SV) support interventions to facilitate comparison over time and across different organizations.MethodsA three-phase qualitative study was conducted from June 2023 to March 2024. This consensus approach engaged members of the European Researchers Network Working on Second Victims. A nominal group technique and insights from a scoping review were used to create a questionnaire for Delphi Rounds. Indicators were rated 1-5, aiming for agreement if over 70% of participants rated an indicator as feasible and sensitive with scores above 4, followed by a consensus conference.ResultsFrom an initial set of 113 indicators, 59 were assessed online, with 35 advancing to the Delphi rounds. Two Delphi rounds were conducted, achieving response rates of over 60% and 80% respectively, resulting in consensus on 11 indicators for evaluating SV support programs. These indicators encompass awareness and activation, outcomes of SV support programs, as well as training offered by the institution.ConclusionThis study presents a scoreboard for designing and monitoring SV support programs, as well as measuring standardized outcomes in future research.